Sustainable Natural Dyes for Textile Use from Food Industry By-Products: A Review - Baaka, Noureddine; Ticha, Manel Ben; Haddar, Wafa; Meksi, Nizar; Dhaouadi, Hatem (Fine Chemical Engineering, 2024)
The valorization of food industry by-products has become very trendy in recent years, several researchers valorized these wastes as sustainable natural colorants for various applications. In this review, the valorization of these by-products in literature as natural dyes in textile application is investigated. Indeed, the history of natural dyes is presented, followed by a study of the advantages and disadvantages of these dyes. Finally, the most significant food industry by-products used as sources of natural dyes for textile applications are listed, along with detailed explanations of their dyeing applications on textile fibers. A special interest is given to natural dyes extracted from food industries wastes of winemaking, olive oil, tomato processing, red pepper by-products and dates paste processing. The majority of studies have demonstrated the strength and superior dyeability of textiles dyed with these waste materials. There have also been assertions that certain fragments have light- and antibacterial-blocking properties.